Report of a Novel Homozygous Nonsense DDR2 Mutation in an Indian Adult Male with Spondylo-meta-epiphyseal Dysplasia, Short Limb-Abnormal Calcification Type - Gupta, Neerja; Correa, Alec Reginald Errol; Jana, Manisha; Kabra, Madhulika (Journal of Pediatric Genetics, 2019)
Spondylo-meta-epiphyseal dysplasia, short limb-abnormal calcification type is a rare autosomal recessive disorder causing severe disproportionate short stature along with typical radiological features. We report an adult male patient with typical features and a novel homozygous nonsense mutation c.2422C > T (p.Gln808Ter) in DDR2. This is the first report of the disease from India.
Keywords: skeletal dysplasia; spondylo-meta-epiphyseal dysplasia; novel mutation; DDR2; exome sequencing